Indole-3-propionic acid alleviates ischemic brain injury in a mouse middle cerebral artery occlusion model - Xie, Yu; Zou, Xiaoxiong; Han, Jianbang; Zhang, Zhongfei; Feng, Zhiming; Ouyang, Qian; Hua, Shiting; Liu, Zhizheng; Li, Cong; Cai, Yingqian; Zou, Yuxi; Tang, Yanping; et al. (Experimental neurology, 2022)
Increasing evidence highlights the importance of gut microbiota and its metabolites as an environmental factor affecting ischemic stroke. However, the role of microbial indole metabolites in ischemic stroke remains largely unknown. Here, we evaluated the effects and the underlying mechanism of indole-3-propionic acid (IPA) in a mouse model of acute middle cerebral artery occlusion (MCAO) and the mechanisms underlying these effects. We collected blood samples and evaluated serum indole derivatives levels using ultra-performance liquid chromatography with tandem mass spectrometry (UPLC-MS) in 8–10-week-old male C57 mice undergoing MCAO or sham. Intragastric IPA administration (400 μg/20 g/d) was performed in mice with MCAO, and its effects and mechanisms were assessed. We found that the serum IPA levels were significantly lower in mice with MCAO than in sham-treated subjects. 16S rRNA gene sequencing revealed that IPA treatment ameliorated the MCAO-induced alterations of the gut microbiome structure, specifically reshaping the microbial community composition in mice with MCAO to resemble that in the mice from the control group, with an increase in the abundance of probiotics and a decrease in the abundance of harmful bacteria. IPA repaired the integrity of the intestinal barrier and regulated the activities of regulatory T cells (Tregs) and Th17 cells in the gut-associated lymphoid tissue. Intragastric IPA administration effectively alleviated neuroinflammation, neurological impairment and brain infarction. Of note, Tregs in the IPA treatment group inhibited A1 reactive astrogliosis in vitro. The beneficial effects of IPA are thus mediated by the gut microbiota, which could enable the development of prebiotics for microbiome-based treatments for ischemic stroke. •IPA levels are reduced after stroke.•IPA improves symptoms of gut and brain disorders.•IPA alters gut microbiota structure after stroke.•IPA inhibites A1 reactive astrogliosis in OGD/R by mediating Tregs.